Variação em encontros consonantais tautossilábicos no português brasileiro - Nivia Aniele Oliveira (2017)
The aim of this dissertation is to analyze the variation in tautosyllabic consonant clusters inBrazilian Portuguese, for example, in [alg] ~ [alg] alegre, among the adult population intwelve Brazilian states. Tautosyllabic consonant clusters are formed by an obstruent and aliquid that occur on the same syllable: alegre or plano. This research is restricted to thetautosyllabic consonant clusters that contain a flap, aiming mainly to assess the lenition thatleads to the cancellation of the flap. It is intended to evaluate the variation in tautosyllabicconsonant clusters in twelve states of Brazil and to consider factors that influence the flaplenition. The theoretical perspective adopted in this dissertation is the Exemplar Theory(JOHNSON, 1997; JOHNSON; MULLENIX, 1997; PIERREHUMBERT, 2001, 2003). Theanalyzed corpus was collected through the website www.fonologia.org, which is composed ofspeech recordings resulting from the reading of a text. The project Sibilants and Rhotics ofBrazilian Portuguese, process: 484590 / 2013-8, Universal Call for Proposals of CNPq, hasthe audio of the reading of this text by 4 speakers of each capital of the twelve states, being aman and a woman equal to or older than 45 years of age and a man and a woman of up to 25years of age. The recording of these readings is between 4 and 5 minutes long each. Two dataanalyses were performed: a categorical and an acoustic one. A total of 1792 data wereanalyzed, with 40 occurrences of consonant clusters for each of the 45 participants. Theresults were analyzed statistically for each of the variables: (1) tonicity, (2) voicing, (3)consonant type, (4) number of syllables, (5) frequency of occurrence, (6) word, (7) region andstate of Brazil, (8) individual, (9) sex and (10) age. The following factors were significant inthe model: stress, consonant type, voicing, number of syllables, age and state. There was nosignificant influence from these factors: sex, frequency of occurrence and type frequency,which were excluded from the final model. The results of the acoustic analysis corroborate theassumptions of the Exemplar Models regarding the gradient of the phenomena of variationand linguistic change. The categorical and acoustic analyses offer indications of the relationbetween phonetic and phonological levels and contribute to the debate about the nature ofmental representations.